Disintegration of phosphatidylcholine liposomes in plasma as a result of interaction with high-density lipoproteins - Scherphof, Gerrit; Roerdink, Frits; Waite, Moseley; Parks, John (Biochimica et biophysica acta, 1978)
1. 1. During in vitro incubation of liposomes or unilamellar vesicles prepared from egg-yolk or rat-liver phosphatidylcholine with human, monkey or rat plasma the phospholipid becomes associated with a high molecular weight protein-containing component. 2. 2. The phosphatidylcholine·protein complex thus formed co-chromatographs with high-density lipoprotein on Ultrogel AcA34 and has the same immunoelectrophoretic properties as this lipoprotein. 3. 3. Release of phosphatidylcholine from liposomes was also observed when liposomes were incubated with pure monkey high-density lipoproteins. Under those conditions some transfer of protein from the lipoprotein to the liposomes was observed as well. 4. 4. The observed release of phospholipid from the liposomes is a one-way process, as the specific radioactivity of liposome-associated phosphatidylcholine remained constant during incubation with plasma. 5. 5. It is concluded that either the lipoprotein particle takes up additional phospholipid or that a new complex is formed from protein constituents of the lipoprotein and the liposomal phosphatidylcholine. 6. 6. Massive release of entrapped 125I-labeled albumin from the liposome during incubation with plasma suggests that the observed release of phosphatidylcholine from the liposomes has a highly destructive influence on the liposomal structure. 7. 7. Our results are discussed with special reference to the use of liposomes as intravenous carriers of drugs and enzymes.